Disharmonisasi Antara Pasal 610 Kitab Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana (KUHP) Baru dan Pasal 12 Undang-Undang Nomor 20 Tahun 2001 Tentang Tidak Pidana Korupsi Terkait Perbuatan Suap - Fazhira Amanda Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to explain the disharmony between Article 610 of Law Number 1 of 2023 concerning the new Criminal Code (KUHP) and Article 12 of Law Number 20 of 2001 concerning Corruption Crimes with regard to acts of bribery, and to examine the resolution of such disharmony between Article 610 of Law Number 1 of 2023 concerning the Criminal Code and Article 12 of Law Number 20 of 2001 concerning Corruption Crimes related to bribery. This research is qualitative in nature and employs a library research design. The results show that, first, the disharmony occurs in the elements of the offense, the scope of regulation, and the consequences of punishment. This is indicated by the similarity of subjects and acts regulated, the absence of an explicit exception clause in the new Criminal Code, and significant differences in criminal sanctions. These conditions have the potential to create legal uncertainty, multiple interpretations, and to weaken the effectiveness of corruption eradication. Second, the resolution of the disharmony should be carried out by prioritizing the principle of lex specialis derogat legi generali, by positioning the Corruption Crimes Law as special criminal legislation in handling bribery offenses.Â